Using the consensus development conference method in healthcare research - Halcomb, E.; Davidson, Patricia; Hardaker, L. (RCN Publishing Company, 2008)
Consensus methods are increasingly being used in healthcare research, particularly for formulating policy and strategic directions. This paper by Elizabeth Halcomb, Patricia Davidson and Laura Hardaker discusses the issues central to the planning and conduct of the consensus development conference, and offers practical recommendations to researchers intending to use this approach